Obesity Incidence with Body Image in Female Adolencence - Wijoyo, Eriyono Budi; Listia Ardiani; Popy Irawati (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
Adolescence is when individuals explore their identities and increase their self-understanding regarding self-image. Body image increases with the individual's satisfaction, who can accept the state of the adolescent's body. One thing that can affect adolescents' body image is obesity. This study aims to determine the relationship between obesity and body image in young women at Health Vocational School, Tangerang City. The research design used is a descriptive correlation with a cross-sectional approach—data collection using the BSQ-34 questionnaire and obesity observation sheet. A total sampling technique was used to take a sample of 35 respondents. The analysis technique used in this study is Chi-Square. This study shows a relationship between obesity and body image among young women in Health Vocational School, Tangerang City. This study shows that obesity is related to body image in young women. Adolescents are expected to behave positively towards their bodies not to cause a negative body image.